Penyebaran Penyakit Brucellosis di Wilayah Koasistensi Administrasi Dinas dan Kesmavet - Roza Azizah Primatika; Bambang Sumiarto; Widagdo Sri Nugroho; Dyah Ayu Widiasih; Yatri Drastini; Doddy Yudhabuntara; Heru Susetya (Jurnal Sain Veteriner, 2021)
Brucellosis is a Brucella bacterial infectious disease that is spread from animals to humans, generally through consumption of milk, especially unpasteurized milk, or other dairy products. Veterinary public health has an important role in preventing transmission of disease to humans through both animals and foodstuffs of animal origin or other animal origin ingredients. Brucellosis is one of the problems often faced by the Animal Husbandry Department, especially at the Animal Health Unit. Handling and controlling about Brucellosis is very vital to maintain animal health and reduce the level of economic losses of farmers due to Brucellosis experienced by livestock owned. This study aims to determine the spread of Brucellosis disease by mapping in the Administrative and Service Coordination areas, to know the handling and control actions carried out by the Animal Husbandry Service throughout the implementation of the Administrative Coordination Office and Veterinary Public Health. The results of the mapping of the spread of Brucellosis in the District of Veterinary Public Health and Public Service Administration Coordination can be divided into 3 groups with the number of cases <10, 10 - 66, and> 66. The number of cases between the range of 10 - 66 there are 3 regions, while the number of cases> 66 there are 2 regions.            Keywords : Brucellosis; Mapping; Handling and Control; Descriptive Statistics